Identificação das proteínas que compõem a glândula prostática do Gerbilo da Mongólia por espectrometria de massas pelo método Shotgun - Garcia Sobrinho, Pedro Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The prostate is a gland found in the reproductive system of humans and rodents of both the male and the female. In males of gerbil (Meriones unguiculatus) prostate gland is divided mainly into three lobes, the dorsum lateral, dorsal and ventral, and these differ in relation to aspects of secretion, the pleating of the epithelium and stromal organization. The ventral lobe of the prostate male gerbils presents morphological similarities with the female prostate of the same, even this gland also features functionally active cells. Many studies show that the development, growth and differentiation prostate are dependent on the action of androgens, being that the primary androgen is testosterone. Thus the depletion and supplementation of testosterone affect morfofisiologicamente both the male prostate gland as female. However, few studies have reported on the types of proteins that may be involved in these changes that affect the male prostates, especially when it comes to proteins found in the female prostate, presents a dysfunctional growth, especially when there are hormonal changes due to lack or excess of testosterone in the body. From this, the aim of this study is to make an analysis of proteomics of the prostates of male and female gerbils adults under normal conditions and subject to depletion and supplementation by testosterone. Therefore, adult male and female gerbils (99 days) were divided into two subgroups for each experimental group: control, neutered and treated, and these received testosterone cypionate for 21 days. The male and female animals of all experimental groups were sacrificed at 120 days of age and then their prostates were removed. Then, the total proteins of the male and female prostates were extracted to be subjected to the technique of mass spectrometry in Shotgun, and the output data of this technique were analyzed by bioinformatics tools thereby, proteomic profile of male and female prostates of gerbil will be...

A próstata é uma glândula encontrada no sistema reprodutor de humanos e roedores do sexo masculino e feminino. Em machos de gerbilo (Meriones unguiculatus), a glândula prostática é dividida principalmente em três lobos: o dorso lateral, dorsal e ventral, sendo que esses apresentam diferenças com relação aos aspectos de secreção, o pregueamento do epitélio e a organização estromal. O lobo ventral prostático de gerbilos machos apresenta similaridades morfológicas com a próstata feminina, pois esta glândula também apresenta células funcionalmente ativas. Estudos mostram que o desenvolvimento, crescimento e a diferenciação prostática são dependentes da ação de andrógenos, sendo que o principal andrógeno é a testosterona. Assim, a depleção e a suplementação pela testosterona afetam morfofisiologicamente tanto a próstata masculina quanto a feminina. Entretanto, poucos estudos relatam sobre os tipos de proteínas que compõem as próstatas masculinas, principalmente quando se trata de proteínas encontradas na próstata feminina. Desse modo, o objetivo desse estudo é fazer uma análise proteômica das próstatas masculinas e femininas de gerbilos adultos em condições normais e submetidas à depleção e a suplementação pela testosterona, utilizando espectrometria de massas. Para isso, gerbilos machos e fêmeas adultos (99 dias) foram divididos em dois subgrupos para cada grupo experimental: controle, castrado e o tratado, sendo que estes receberam cipionato de testosterona (1mg/Kg/dia) durante 21 dias. Os animais machos e fêmeas de todos os grupos experimentais foram sacrificados com 120 dias de idade e em seguida, as próstatas foram retiradas e a fração proteica extaída para análise por espectrometria de massas no contexto Shotgun. Os dados resultantes dessa técnica foram analisados com ferramentas de bioinformática. Esta investigação possibilitaou identificar...
Keywords: Biologia molecular; Biofísica; Proteínas; Proteômica; Gerbilos; Próstata; Hormonios; Espectrometria de massa